An unfamiliar America : essays in American studies - Helo, Ari; Saikku, Mikko (New York, NY : Routledge, 2021)
"This collection focuses on conceptions of the unfamiliar from the viewpoint of mainstream American history: aliens, immigrants, ethnic groups, and previously unencountered ideas and ideologies in Trumpian America. The book suggests bringing historical thinking back to the center of American Studies, given that it has been recently challenged by the influential memory studies boom. As much as identity-building appears to be the central concern for much of the current practice in American history writing, it is worth keeping in mind that historical truth may not always directly contribute to one's identity-building. The researcher's constant quest for truth does not equate to already possessing it. History changes all the time, because it consists of our constant reinterpretation of the past. It is only the past that does not change. This collection aims at keeping these two apart, while scrutinizing a variety of contested topics in American history, from xenophobic attitudes toward eighteenth-century university professors, Apache masculinity, Ku Klux Klan, Tom Waits's lyrics, and the politics of the Trump era"--
OCLC-licensed vendor bibliographic record.
Keywords: Xenophobia -- United States -- History; Racism -- United States -- History; Minorities -- United States -- Social conditions; Minorities -- Civil rights -- United States -- History; Christianity and politics -- United States; National characteristics, American; United States -- Race relations -- History; United States -- Ethnic relations -- History; United States -- Politics and government -- 2017-; HISTORY / United States / General; HISTORY / Social History